Plant microbiome analysis after Metarhizium amendment reveals increases in abundance of plant growth-promoting organisms and maintenance of disease-suppressive soil - Barelli, Larissa; Waller, Alison S.; Behie, Scott W.; Bidochka, Michael J. (PLOS ONE, 2020)
The microbial community in the plant rhizosphere is vital to plant productivity and disease resistance. Alterations in the composition and diversity of species within this community could be detrimental if microbes suppressing the activity of pathogens are removed. Species of the insect-pathogenic fungus, Metarhizium, commonly employed as biological control agents against crop pests, have recently been identified as plant root colonizers and provide a variety of benefits (e.g. growth promotion, drought resistance, nitrogen acquisition). However, the impact of Metarhizium amendment on the rhizosphere microbiome has yet to be elucidated. Using Illumina sequencing, we examined the community profiles (bacteria and fungi) of common bean (Phaseolus vulgaris) rhizosphere (loose soil and plant root) after amendment with M. robertsii conidia, in the presence and absence of an insect host. Although alpha diversity was not significantly affected overall, there were numerous examples of plant growth-promoting organisms that significantly increased with Metarhizium amendment (Bradyrhizobium, Flavobacterium, Chaetomium, Trichoderma). Specifically, the abundance of Bradyrhizobium, a group of nitrogen-fixing bacteria, was confirmed to be increased using a qPCR assay with genus-specific primers. In addition, the ability of the microbiome to suppress the activity of a known bean root pathogen was assessed. The development of disease symptoms after application with Fusarium solani f. sp. phaseoli was visible in the hypocotyl and upper root of plants grown in sterilized soil but was suppressed during growth in microbiome soil and soil treated with M. robertsii. Successful amendment of agricultural soils with biocontrol agents such as Metarhizium necessitates a comprehensive understanding of the effects on the diversity of the rhizosphere microbiome. Such research is fundamentally important towards sustainable agricultural practices to improve overall plant health and productivity.